2015
DOI: 10.2169/internalmedicine.54.2828
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Manifestations of Tuberculosis-associated Immune Reconstitution Inflammatory Syndrome during Adalimumab Therapy: A Case Report and Review of the Literature

Abstract: A 64-year-old neurologically asymptomatic woman with rheumatoid arthritis who was treated with the tumor necrosis factor (TNF)-α antagonist adalimumab developed disseminated tuberculosis (TB). After receiving anti-TB therapy and discontinuing adalimumab, she exhibited paradoxical worsening due to immune reconstitution inflammatory syndrome (IRIS) with the appearance of meningitis and brain tuberculomas. This case indicates that continuing anti-TNF therapy may be necessary to prevent IRIS in patients who develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…5,6,24,25 Methotrexate is used for the treatment of pancreatic cancer, but has been shown to destroy the beta cells of the pancreas, primarily through oxidative stress. 5,6,[24][25][26] A decrease in islets of Langerhans insulin and somatostatin-immunopositive cells was shown in this study following the administration of MTX (Fig. 2B, 3B).…”
Section: A B Csupporting
confidence: 64%
See 1 more Smart Citation
“…5,6,24,25 Methotrexate is used for the treatment of pancreatic cancer, but has been shown to destroy the beta cells of the pancreas, primarily through oxidative stress. 5,6,[24][25][26] A decrease in islets of Langerhans insulin and somatostatin-immunopositive cells was shown in this study following the administration of MTX (Fig. 2B, 3B).…”
Section: A B Csupporting
confidence: 64%
“…4,5,10,11,19,27 It has been experimentally proven that TNF inhibitors prohibit organ tissue damage by suppressing the formation of TNF-α, proinflammatory cytokines, and nitric oxide. 5,26,27 A decrease in edema, acinar cell edema, and necrotic cells was observed in Group 3 (p < 0.05) ( Table 2) after the administration of ADA. An increase in islets of Langerhans insulin and somatostatin-positive cells was also demonstrated following the application of ADA treatment to Group 3 (Fig.…”
Section: A B Cmentioning
confidence: 88%
“…Risk factors of IRIS in a patient undergoing treatment with tumor necrosis factor (TNF)-α inhibitors (TNFIs) are disseminated TB, history of TB, and use of steroids at diagnosis [9,10]. In the TB patient without HIV infection it has been reported that IRIS is not related to the immunosuppressed state [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, IRIS was recognized as lymphadenopathy and the appearance of a new polyp-like lesion in the trachea after discontinuing adalimumab and receiving anti-tuberculosis treatment. As with IRIS in HIV-infected pa-tients (11), corticosteroid therapy is usually required to treat IRIS that develops after discontinuing anti-TNFα therapy, although there is a lack of good supporting evidence (12). Controversy also exists concerning the continuation of anti-TNFα therapy in patients who develop tuberculosis (13,14).…”
Section: Discussionmentioning
confidence: 99%